Pertautan Epistemologi Bayani dan Pendidikan Islam Masa Keemasan - Mahmud Arif (Al-Jami'ah: Journal of Islamic Studies, 2002)
Historically, the current Islamic thought is essentially a continuation of the result of Islamic thought theorizing that peaked in the Golden ages (III - V H). As a consequence of bayaniyyun domination the product of Islamic thought in the Golden ages has succeeded to build an image that Islamic Arabic thought inherited by us currently is nothing but an "Islamic law" civilization. This can be viewed from epistemological fact; the wriggle of Islamic Arabic thought is always present at the firm hegemony of bayani reason structure attaining a supremacy momentum from Islamic humanism and scholasticism movements.Furthermore, the bayani reason structure has subsequently permeated into Islamic education as a cultural "reason" for education at that time. Then, this permeating has caused appearing of "the religious-conservative" education school that less is appreciated to every rational impact from "outside", so that tends to make marginal intellectual sciences. It was natural in its development, "intellectualism" becomes overcast from the realm of Moslem consciousness. This reality has been made worse by madrasa as a par excellence institution in the Islamic world that has changed its function as only a "wagon" mover of bayani tradition. This article tries to investigate the process of awakening of bayani epistemology and its linkage with Islamic Education in the Golden ages with Islamic education in the Golden ages.